2022
DOI: 10.3390/cancers14040914
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Feasibility and Acceptability of an Artificial-Intelligence-Enabled and Speech-Based Distress Screening Mobile App for Adolescents and Young Adults Diagnosed with Cancer: A Study Protocol

Abstract: Adolescents and young adults (AYAs) diagnosed with cancer are an age-defined population, with studies reporting up to 45% of the population experiencing psychological distress. Although it is essential to screen and monitor for psychological distress throughout AYAs’ cancer journeys, many cancer centers fail to effectively implement distress screening protocols largely due to busy clinical workflow and survey fatigue. Recent advances in mobile technology and speech science have enabled flexible and engaging me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 62 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…A few studies are beginning to ask important questions about overall acceptability of such advances including use of AI platforms to monitor distress. 43 Patient engagement also requires aligning goals so that their health data are not exploited for the financial gain of developers and institutions while patients continue to face escalating cancer costs. Nefarious use and those not aligned with patient needs and wellbeing need to be anticipated.…”
Section: Perils Of Llmsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies are beginning to ask important questions about overall acceptability of such advances including use of AI platforms to monitor distress. 43 Patient engagement also requires aligning goals so that their health data are not exploited for the financial gain of developers and institutions while patients continue to face escalating cancer costs. Nefarious use and those not aligned with patient needs and wellbeing need to be anticipated.…”
Section: Perils Of Llmsmentioning
confidence: 99%
“…A few studies are beginning to ask important questions about overall acceptability of such advances including use of AI platforms to monitor distress. 43…”
Section: Perils Of Llmsmentioning
confidence: 99%
“…The hope is that through greater collaborations with technology companies, greater efficiencies may be built into the clinical workforce and more artificial intelligences can be built into program design. In this way, standardized programs may still be individualized if rules and logic are able to construct a psychological package that matches to the individual’s personal profile [ 21 ]. This is a leap from traditional manualized interventions that are offered as a one size fits all model.…”
Section: All Things Digital: Telehealth Opportunities and Challengesmentioning
confidence: 99%
“…With the outbreak of the COVID-19 pandemic, social isolation has become an even more critical problem, preventing adolescents with CPMCs from socializing not only with their peers but also with family members and other members of their support networks [13][14][15]. A number of mobile apps and web-based interventions have emerged to help patients with CPMCs to deal with stress [16], social isolation [17,18], anxiety [19], depression [19,20], symptom burden [16], and disease management [21,22]. Although numerous studies have shown a positive impact of these apps [16][17][18][20][21][22], none of the app-based interventions that we reviewed had social elements that would allow patients to interact with their peers or members of their support networks.…”
Section: Introductionmentioning
confidence: 99%
“…A number of mobile apps and web-based interventions have emerged to help patients with CPMCs to deal with stress [16], social isolation [17,18], anxiety [19], depression [19,20], symptom burden [16], and disease management [21,22]. Although numerous studies have shown a positive impact of these apps [16][17][18][20][21][22], none of the app-based interventions that we reviewed had social elements that would allow patients to interact with their peers or members of their support networks. Moreover, we were unable to find the majority of the apps described in the reviewed studies on publicly available app stores such as Apple App Store, Google Play Store, or Steam, suggesting that the apps used as part of research studies either were not available to the general public or did not have long-term support from the developers.…”
Section: Introductionmentioning
confidence: 99%